Aspectos comportamentais na criação de insetos envolvidos no controle biológico da Diatraea Flavipennella - Silva, Roberto Balbino da (2019)
Paraíba is prominent in the sugarcane production, being the third state with highest productive impact in the Northeast. In the 2018/2019 harvest, the state processed 5,675,107.870 million tons destined to the production of 118 thousand tons of sugar and 382 thousand m³ of ethanol. Among the multiple aspects that permeate the sugarcane culture, this study focus on the biological control, more precisely the biological cycle and behavioral aspects of Cotesia flavipes and Diatraea saccharalis produced in laboratory, on the Paraíba north coast. The research experiments were carried out at the Mass Production of Biological Control Laboratory (LPMCB) of the Paraíba Sugarcane Growers Association (ASPLAN), in Mamanguape, the north coast of Paraíba. Regarding the C. flavipes insects there were measured the egg-larva duration; the pupa duration; the quantitative of adults; the number of cocoons per caterpillar; the pupae viability; the sex ratio at the three temperatures (21, 25 and 29oC) and the efficiency among male and female handlers. Regarding the D. saccharalis pest host behavioral variables, it was observed the D. saccharalis egg-adult biological cycle, the larvae and pupae viability, adult sex ratio and the number of larvae per couple. In the first stage, corresponding to the egg-adult life biological cycle evaluation, the experiment used 34 couples randomly selected from the laboratory commercial creation, individually accommodated. In the second stage, to diagnose the larva-pupa, larva-adult and pupa-adult viability, as well as the D. saccharalis adult sex ratio, 600 larvae were collected during five weeks, 120 units per week. In the third stage, regarding the experiment evaluations to measure the number of larvae per couple, it was necessary to perform four treatments with 10 repetitions each, using one adult couple of insects per mating chamber. As analysis of variance was performed and the average was compared through the statistical program of the Student Newlman Keuls Test – Cloud Radio Access Networks (CRAN) version 2019. In the results obtained by the study, the laboratory-produced parasitoids behavioral aspects present differences among the controlled temperatures. Concluding that the parasitoid sample presents satisfactory quality to the analyzed parameters and that temperature is an important factor to extend or reduce the C. flavipes and D. saccharali life cycle.